2012
DOI: 10.1063/1.4745935
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure at morphotropic phase boundary in Pb(Mg1/3Nb2/3)O3-PbTiO3 ceramic: Coexistence of nano-scaled {110}-type rhombohedral twin and {110}-type tetragonal twin

Abstract: For more than half a century, the morphotropic phase boundary (MPB) has drawn constant interest in developing piezoelectric materials, as the phase instability at the region significantly enhances piezoelectricity. However, the local structure/symmetry at the MPB region is still under controversy. The investigation on morphology and origin of the local structure at MPB is of considerable importance to provide a microstructure basis for high piezoelectricity. In the present study, we thus use high resolution tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 57 publications
5
30
0
Order By: Relevance
“…In fact, the PMN-25PT composition lies close to a possible tricritical point where a second order phase transition arises in the x-T phase diagram. 36 The critical point in polycrystalline PMN-xPT system is also likely to be diffuse in nature due to the observed orientational heterogeneity or even absence of critical point depending on the electric field direction. 35,[37][38][39][40] The temperature of the maximum ECE responsivity was observed to lie just above T d (¼ T C ) (extrapolated from Figure 4) which is reflected in their similar concentration dependence ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the PMN-25PT composition lies close to a possible tricritical point where a second order phase transition arises in the x-T phase diagram. 36 The critical point in polycrystalline PMN-xPT system is also likely to be diffuse in nature due to the observed orientational heterogeneity or even absence of critical point depending on the electric field direction. 35,[37][38][39][40] The temperature of the maximum ECE responsivity was observed to lie just above T d (¼ T C ) (extrapolated from Figure 4) which is reflected in their similar concentration dependence ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Monoclinic (M) or orthorhombic (O) adaptive phases with nanoscale textures and low-symmetry phases with nanotwin diffraction in the MPB region have been proposed based on x-ray diffraction (XRD), neutron diffraction, and transmission electron microscopy (TEM) analyses. [7][8][9][10][11][12][13] So far, the microstructure of lead zirconate titanate Pb(Ti 1Àx Zr x ) O 3 (PZT) and (1Àx)Bi 0.5 Na 0.5 TiO 3 -xBaTiO 3 (BNT-BT) close to the morphotropic phase boundary (MPB) remains unclear, and is even controversially reported by different groups. [12][13][14][15][16] On the other hand, polycrystalline materials must be poled by electric fields in order to exhibit piezoelectricity.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that the existence of nanodomains is a common feature of the MPB region [18,19,[25][26][27][28][29][30][31]. It has been reported that the nanodomains, whose size is much smaller than the coherence length of diffraction radiations, scatter waves from individual nanodomains coherently superimposed in diffraction profiles, and cause anisotropic broadening, asymmetries, intensity distribution variation between the peaks, and even new peaks appearance in diffraction patterns [31,32].…”
Section: Introductionmentioning
confidence: 99%